1980
DOI: 10.1002/1097-0142(19800801)46:3<595::aid-cncr2820460328>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary osteogenic sarcoma of the vertebral column. A clinicopathologic correlation of ten patients

Abstract: In a review of more than 1000 patients with osteogenic sarcoma of bone, the vertebral column was the site of the primary tumor in 10 patients. The vertebral osteogenic sarcoma in 4 of the 10 patients was secondary; to Paget's disease of bone in 3, and to irradiation received for a prior cancer in 1. Frequently, cord compression caused severe neurologic symptoms. Prognosis was always poor. Seven patients died of their disease within a year of histologic diagnosis. The differential diagnoses between osteogenic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 19 publications
3
63
1
Order By: Relevance
“…2,3,5,24,25 Primary osteosarcoma of the spine accounts for 1.2% of all patients in this series, which is very similar to previous reports. 3,4,24 Twenty of 22 patients had pain, and 12 of 22 patients had a neurologic deficit.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…2,3,5,24,25 Primary osteosarcoma of the spine accounts for 1.2% of all patients in this series, which is very similar to previous reports. 3,4,24 Twenty of 22 patients had pain, and 12 of 22 patients had a neurologic deficit.…”
Section: Discussionsupporting
confidence: 90%
“…There are only a few reports on long-term survivors of spinal osteosarcoma after receiving chemotherapy with 3 or without radiation therapy. 15 In general, however, the effect of chemotherapy is only temporary, and preoperative chemotherapy should be followed by intensive local treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Osteosarcoma is a malignant bone tumor that frequently affects patients in their second and third decades of life, however, it is reported there exists two peaks in the incidence of osteosarcoma, one is in the second decade and another in the seventh decade of life. 7 Huvos 8 reported three cases of osteosarcoma of the spine among 117 patients with osteosarcoma older than 60 years.…”
Section: Introductionmentioning
confidence: 99%
“…3 It tends to occur in a slightly older age group, with a mean age of 38 years, 4 than osteosarcoma of the extremity. 3,5,6 It has been found that the prognosis for patients with osteosarcoma of the trunk is worse compared with the prognosis of patients with osteosarcoma of the extremities. 3,5,7 In recent years, aggressive adjuvant and neoadjuvant chemotherapy has improved the treatment outcome of patients with osteosarcoma.…”
mentioning
confidence: 99%